New records of biting midges (Diptera: Ceratopogonidae) from Tabasco, Mexico - Heron Huerta; Luis Miguel Rodríguez-Martínez; José Ismael Benitez-Alva; Felipe Dzul-Manzanilla; Pablo Manrique-Saide (Revista Mexicana de Biodiversidad)
New distribution records for the state of Tabasco of the following species are presented: Forcipomyia stylifer (Lutz, 1913), Culicoides blantoni Vargas & Wirth, 1955, Culicoides foxi Ortiz, 1950, Culicoides leopoldoi Ortiz, 1951, Culicoides jamaicensis Edwards, 1922, Culicoides poikilonotus Macfie, 1948 and Stilobezzia coquilletti Kieffer, 1917; and new locality records for Culicoides gabaldoni Ortiz, 1954, Culicoides insignis Lutz, 1913, Culicoides paraensis (Goeldi, 1905) and Stilobezzia kiefferi Lane, 1947. We confirmed the distribution record of Culicoides dicrourus Wirth & Blanton, 1955 from Mexico. A key and an updated list for the known species of Culicoides Latreille, 1809 from the state of Tabasco is also provided.